Growth dynamics of young fattened bulls measured by non-stress methods at the commercial feedlot - Jeník, David; Kopec, Tomas; Chládek, Gustac; Falta, Daniel (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2023)
The experiment aimed to evaluate the growth ability of Czech Fleckvieh Simmental bulls at the beginning of fattening in the conditions of a modern commercial stable on a private farm. A total of 40 bulls were included in the experiment, which were moved to the stable at the age of 2 months, and the measurements were carried out up to 8 months of age. The bulls were measured at regular intervals of 14 days using a device that eliminates the stress of the animals and thereby increases their welfare. The measurement was carried out using a non-stress device, the live weight of the animals and the withers height were recorded. The net weight gain was determined from the measured data, which reached an average of 1.14 kg/day during the entire experiment. In addition, the growth curve was evaluated using the measured values of live weight and height at withers. The animals at 60 days had an average weight of 106 kg and a height at withers of 86.3 cm. At 120 days, the average weight was 167.3 kg and the height was 95.3 cm. At the age of 210 days, the average weight of the bulls was 283.6 kg and the height was 109.7 cm. The correlation coefficients between measured live weight and height at withers was 0.94 (p